Other histories. New historical approaches in ethnomusicology (Revista Argentina de Musicología, 2023)
Towards the end of the 1970s, Zofia Lissa wrote that historical musicology left the study of the living cultures of the world to ethnomusicology. The Polish musicologist maintained that the price paid for this was the acceptance of an ahistorical view, limited to exposing the current state of the culture studied without delving into its development processes. Although the criticism seems justified at first glance, a deeper analysis suggests that the historical concern on the part of those who practiced ethnomusicology was no less than that of colleagues in the field of music history. Both topics such as the origin of music and the migratory routes of musical techniques and instruments—so central to early comparative musicology—were based on concerns of a historical nature and, even in the seventies, a prestigious ethnomusicologist like Klaus Wachsmann had stated that The present that the ethnomusicologist found in the fieldwork encompassed parts of the past because it contained the personal memories of the informants, the collective memory of the group and material remains such as instruments, recordings, musical paraphernalia or written sources. It was only as a result of the so-called historical turn in Anglo-Saxon ethnomusicology that, in Latin America, we began to systematically reﬂect on how history had been written and on how we were writing or rewriting history. Becoming aware of the conﬂuence of these two traditions was what led me to devise the dossier on ethnomusicology and history that I now present.